A PERSONAL, DEBATABLE AND TIMELY VIEW ON WORLD ORDER: HENRY KISSINGER – HENRY KISSINGER – WORLD ORDER, PENGUIN PRESS, NEW YORK, 2014 - Book review - FLORIN BONCIU (Global Economic Observer)
The concept of World Order had been much more present in the scientific debates and mass-media before 1990 when the world economy were more or less bipolar and the ideas of a dynamic balance of power and of spheres of influence were logically justified. After 1990 at the end of the Cold War a rather false perception became prevalent, particularly in the Western countries, projecting a unipolar world gradually witnessing a universalization of the Western style liberal democracy. This was epitomized in Francis Fukuyama’s book “The End of History and the Last Man”.